1986
DOI: 10.1007/bf00925477
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of myotropic and macrophagotropic strains ofTrypanosoma cruzi with myoblasts and fibers of skeletal muscle

Abstract: The process of interaction of bloodstream trypomastigotes from the myotropic CL and Colombiana strains and the macrophagotropic Y strain of Trypanosoma cruzi with mouse myoblasts and myotubes was analysed. After 24 h of parasite-host cell interaction, parasites from the CL and Colombiana strains appeared to be more infective to myoblasts than those from the Y strain. Parasites from the Colombiana strain were more infective for myotubes than those from the Y strain, while those from the CL strain showed very a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Similar observations of differences in infectivity of myoblasts by distinct T. cruzi populations have been described (Araújo et al 1986). These authors showed that in the first 24 h of parasite-host cell interaction, T. cruzi CL and Colombian strains, generally considered myotropic (Melo & Brener 1978, Camandaroba et al 2001, were much more infective to myoblasts than the T. cruzi Y strain, considered macrophagotropic (Melo & Brener 1978).…”
supporting
confidence: 71%
“…Similar observations of differences in infectivity of myoblasts by distinct T. cruzi populations have been described (Araújo et al 1986). These authors showed that in the first 24 h of parasite-host cell interaction, T. cruzi CL and Colombian strains, generally considered myotropic (Melo & Brener 1978, Camandaroba et al 2001, were much more infective to myoblasts than the T. cruzi Y strain, considered macrophagotropic (Melo & Brener 1978).…”
supporting
confidence: 71%
“…L6, along with THP-1, presented a superior ratio of infected cells but yielded a lower number of intracellular amastigotes/infected cells for Y-H10 infection, when compared to other lines (Table 1, Figure S1). T. cruzi Y strain is classified as highly macrophagotropic rather than myotropic [29,42,43]; therefore, the in vitro invasion of a macrophage-like cell by this strain may be favored in comparison to the other cell lines. Interestingly, Sylvio X10/1 promoted lower infection of L6 cells, with rates almost three times lower than observed for Y-H10 infected L6 cells (Table S1); probably the divergence in a myoblast cell line (L6) infectivity profile between the strains could be associated with strain-specific “tropism,” which might as well be the result of a combination of the variables mentioned above [43].…”
Section: Discussionmentioning
confidence: 99%
“…The great potential of the in vitro models is the study of the interaction T. cruzihost cell throughout amastigote culture. It has been demonstrated the in vitro capacity of invasion in all cell types was tested [10,24]. As yet, in vivo models, infected animals, as well as in human, show evidence of a parasite tropism by cells of the mononuclear phagocytic system and by muscle and nerve cells, contrary to what is observed in vitro as mentioned before.…”
Section: Advantages and Limitation Of In Vitro Trypanosoma Cruzi Culturementioning
confidence: 86%
“…Intracellular amastigote can release within 72 h trypomastigote metacyclic from culture derived. Infected Vero cells can be in continuous cultivation during 6-8 weeks [10].…”
Section: How To Maintain and Cultivate Trypanosoma Cruzi?mentioning
confidence: 99%